Preparation of porous carbons based on polyvinylidene fluoride for CO2 adsorption: A combined experimental and computational study - Hong, Seok-Min; Lim, Geunsik; Kim, Sung Hyun; Kim, Jong Hak; Lee, Ki Bong; Ham, Hyung Chul (ELSEVIER SCIENCE BV, 2016)
Microporous carbons were developed for CO2 capture from polyvinylidene fluoride (PVDF) via a simple carbonization method. The carbonization was carried out in the temperature range of 400-800 degrees C, and the effects of the carbonization temperature on the characteristics and CO2 adsorption behavior of the prepared carbon materials were investigated by both experiments and density functional theory studies. The textural characteristics of the carbon materials were highly dependent on the carbonization temperature, and narrow micropores (<0.7 nm) were predominantly generated from the decomposition of PVDF giving off fluorine during carbonization. The specific surface area and pore volume increased up to 1011 m(2) g(-1) and 0.416 cm(3) g(-1), respectively, and the highest CO2 adsorption capacity of 3.59 mol kg(-1) was obtained at 25 degrees C and similar to 1 bar in PVDF carbonized at 800 degrees C. The carbonized PVDFs also exhibited highly stable CO2 adsorption uptake and rapid kinetics through repeated adsorption-desorption cycles, showing that carbonized PVDFs are promising adsorbents for CO2 capture. The density functional theory calculation suggested that stable configuration with favorable adsorption energy can be introduced by the removal of fluorine from PVDF, which results in the reduction of repulsive interactions between electronegative fluorine in PVDF and oxygen in CO2 molecule. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: HIGH-SURFACE-AREA; POLY(VINYLIDENE FLUORIDE); ACTIVATED CARBON; MICROPORE SIZE; PERFORMANCE; FIBERS; MORPHOLOGY; PYROLYSIS; CAPACITY; SORPTION